STUDI STRATEGI PEMASARAN DAN KEUNTUNGAN UMKM KOPI SEMENDE CAP BUNGA DI KELURAHAN 16 ULU KECAMATAN SEBERANG ULU II PALEMBANG SUMATERA SELATAN - Yulianto, Preli; Abubakar, Rafeah (Universitas Muhammadiyah Palembang, 2021)
This research purpose are to know the marketing strategy and calculate the production profits of UMKM Kopi Semende Cap Bunga. This research was conducted in 16 Ulu Village, Seberang Ulu II Palembang District, South Sumatra from July to August 2020. This research used a case study method with qualitative and quantitative descriptive approaches. The sampling method used was purposive sampling. For of data collection using observation method with interviews using questionnaires, and supported by documentation. To answer the first problem, using qualitative analysis and for the second problem formulation using profit analysis. Based on the results of the research, it can be concluded that marketing mix, namely the 4P (product, price, place, promotion) has been implemented but, it has not been maximized, especially in the marketing mix of places related to distribution channels, and promotional marketing mix due to limited human resources. UMKM Kopi Semende Cap Bunga during the production process collected revenue of Rp. 30,000,000 with a total cost of Rp. 16,670,375 and get profit Rp. 13,329,625 production process.